The Integrated Case Management Manual Value-Based Assistance to Complex Medical and Behavioral Health Patients - Kathol, Roger G. (Springer International Publishing, 2018)
Thoroughly revised and updated since its initial publication in 2010, the second edition of this gold standard guide for case managers again helps readers enhance their ability to work with complex, multimorbid patients, to apply and document evidence-based assessments, and to advocate for improved quality and safe care for all patients. Much has happened since Integrated Case Management (ICM), now Value-Based Integrated Case Management (VB-ICM), was first introduced in the U.S. in 2010. The Integrated Case Management Manual: Valued-Based Assistance to Complex Medical and Behavioral Health Patients, 2nd Edition emphasizes the field has now moved from "complexity assessments" to "outcome achievement" for individuals/patients with health complexity. It also stresses that the next steps in VB-ICM must be to implement a standardized process, which documents, analyzes, and reports the impact of VB-ICM services in removing patient barriers to health improvement, enhancing quality and care coordination, and lowering the financial impact to patients, providers, and employer groups. Written by two expert case managers who have used VB-ICM in their large fully disseminated VB-ICM program and understand its practical deployment and use, the second edition also includes two authors with backgrounds as physician support personnel to case managers working with complex individuals. This edition builds on the consolidation of biopsychosocial and health system case management activities that were emphasized in the first edition. A must-have resource for anyone in the field, The Integrated Case Management Manual: Value-Based Assistance to Complex Medical and Behavioral Health Patients, 2nd Edition is an essential reference for not only case managers but all clinicians and allied personnel concerned with providing state-of-the-art, value-based integrated case management.